Penerapan Upaya Pengolahan Kualitas Data Untuk Meningkatkan Informasi yang Konsisten - Lubis, Rizky Amalia; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In the fast-paced and dynamic digital era, data is an important asset in supporting the right decision-making process. However, the high volume of data generated every day requires a data processing system that is not only accurate but also consistent. Consistency of information is the main key in maintaining data reliability as a basis for analysis and policy. This material discusses in full various strategic efforts in improving the quality of data processing, which include standardization of work procedures, implementation of data validation and verification systems, integration of sophisticated information technology, and increasing the competence and awareness of human resources in data management. In addition, this material also highlights the importance of good data governance, ongoing supervision, and a work culture that is oriented towards information quality. Through these approaches, it is hoped that organizations or agencies will be able to create information systems that are not only reliable but also consistent in the long term. This consistency is an important foundation in supporting operational effectiveness and the success of digital transformation as a whole.